Hope, trust and segregation in schools: An analysis of contextual effects on violent and general offending - Sandahl, Julia (The British journal of criminology, 2021)
Influenced by the theoretical concepts of ‘Relative deprivation’ and ‘Social cohesion’, this study adds to the relatively limited literature of socio-structural approaches to the school-crime relationship. Multilevel analysis was conducted to explore the independent and interactive effects of three distinct features of the school setting—concentrated (dis)advantage, the proportion of students with poor future prospects and teacher-rated social cohesion—in relation to self-reported offending. Using information from three data sources on 4,608 students and 1,056 teachers from 77 lower secondary schools in Stockholm, the results showed that school concentrated (dis)advantage and school-level future prospects were directly related to offending. In addition, cross-level interactions indicate that the association between student performance and offending differs depending on school type.